2018
DOI: 10.1016/j.ijheatmasstransfer.2018.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of natural convection heat transfer in inclined and fully divided CO2 enclosures on Mars

Abstract: This is a repository copy of Theoretical investigation of natural convection heat transfer in inclined and fully divided CO enclosures on Mars ₂ .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Selimefendigil and Öztop [17] used the finite element method to investigate conjugate natural convection and conduction heat transfer in an inclined partitioned cavity filled with different nanofluids on different sides of the partition. Sun et al [18] presented extensive numerical studies on fluid flow and heat transfer in inclined and fully divided CO 2 enclosures with partitions on Mars. It was observed that three flow regimes formed in succession when the tilt angle increased, namely, Rayleigh-Bénard convection, transition convection, and single-cell convection.…”
Section: Introductionmentioning
confidence: 99%
“…Selimefendigil and Öztop [17] used the finite element method to investigate conjugate natural convection and conduction heat transfer in an inclined partitioned cavity filled with different nanofluids on different sides of the partition. Sun et al [18] presented extensive numerical studies on fluid flow and heat transfer in inclined and fully divided CO 2 enclosures with partitions on Mars. It was observed that three flow regimes formed in succession when the tilt angle increased, namely, Rayleigh-Bénard convection, transition convection, and single-cell convection.…”
Section: Introductionmentioning
confidence: 99%